Hello Stranger - Center, Katherine (New York : St. Martin's Press, 2023)
"Sadie Montogmery has had good breaks and bad breaks in her life, but as a struggling artist, all she needs is one lucky break. Things seem to be going her way when she lands one of the coveted finalist spots in a portrait competition. It happens to coincide with a surgery she needs to have. Minor, they say. Less than a week in the hospital they say. Nothing about you will change, they say. Upon recovery, it begins to dawn on Sadie that she can see everything around her, but she can no longer see faces. Temporary, they say. Lots of people deal with this, they say. As she struggles to cope-and hang onto her artistic dreams-she finds solace in her fourteen-year-old dog, Peanut. Thankfully, she can still see animal faces. When Peanut gets sick, she rushes him to the emergency vet nearby. That's when she meets veterinarian Dr. Addison. And she's pleasantly surprised when he asks her on a date. But she doesn't want anyone to know about her face blindness. Least of all Joe, her obnoxious neighbor who always wears a bowling jacket and seems to know everyone in the building. He's always there at the most embarrassing but convenient times, and soon, they develop a sort of friendship. But could it be something more? As Sadie tries to save her career, confront her haunting past, and handle falling in love with two different guys she realizes that happiness can be found in the places-and people- you least expect"--.
new book 2023 summer.
Keywords: Romance; Life change events; Man-woman relationships; Self-realization in women; Novels; Romance fiction